A survey (2010) of fish population in a disused mining pool near the UPM swimming pool at Universiti Putra Malaysia, Serdang, Selangor - Kamaruddin, Izharuddin Shah; Mustafa Kamal, Abdul Satar (Centre for Extension, Entrepreneurship and Professional Advancement (APEEC), Universiti Putra Malaysia, 2010)
A survey of fish population was carried out in a disused mining pool which located near to Universiti Putra Malaysia’s (UPM) swimming pool at UPM Serdang, Selangor. This pool was named as Swimming Pool Pond (SP Pond). Fish sampling was conducted in March 2010 by using gill nets with a mesh size of 6.35 cm, at three sampling stations which designated as station A, station B and station C. These nets were set at dusk and hauled in the next morning and a total of 36 individual fishes from 6 species were captured from the survey. The fish population was comprises of Osteochilus hasselti (Terbol) (36.1%), Notopterus notopterus (Belida) (27.8%), Cyclocheilichthys apogon (Temperas) (25.0%), Channa micropeltes (Toman) (5.6%), Hemibagrus nemurus (Baung) (2.8%) and Oreochromis niloticus (Tilapia) (2.8%). The fish diversity indices obtained from this survey shows that the Shannon-Weaver index value was 1.43, Pielou’s evenness index value was 0.80 and Margalef’s species richness index value was 3.21. Results obtained from this survey might be useful in pond management especially for fish re-stocking programmes, in which the latest technology or methods in hatcheries would be involved to prepare the juvenile or adult fish into fish stock.